Digitally focused array ultrasonic testing technique for carbon fiber composite structures; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Salchak Ya. A. Yana Alekseevna; Zhvyrblya V. Yu. Vadim Yurievich; Sednev D. A. Dmitry Andreevich; Lider A. M. Andrey Markovich (2016, 2016)
Title screen